ANALISIS TRANSPARANSI, EFEKTIVITAS, DAN EFISIENSI PENGELOLAAN KEUANGAN DAERAH BERBASIS WEBSITE PEMERINTAH DAERAH SULAWESI TENGAH - Luneto, Abdul Razik; Widyakusuma, Annastry; Darmawan, I Putu Edi; Kadim, Immawan Muhajir (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2025)
This study examines the transparency, effectiveness, and efficiency of financial management in 13 district/city governments in Central Sulawesi using a descriptive qualitative approach with the content analysis method. Data were obtained from the official website of the regional government for the 2023 budget year and measured based on transparency indicators at the planning, implementation, and reporting and accountability stages of the APBD. The results of the study show that Banggai Laut Regency has the highest transparency index (98.28%), while Toli-Toli Regency has the lowest (27.59%). The average level of financial management effectiveness reaches 93%, categorized as effective, although there are disparities between regions. The main obstacles to transparency lie in limited infrastructure and human resource capacity. These findings emphasize the importance of technological support, human resource training, and provincial government policies to encourage transparency and accountability of regional finances in a sustainable manner. Keywords: Transparency of Financial Management, Effectiveness of Regional Finances of District/City Governments